Because of Winn-Dixie - DiCamillo, Kate (Scholastic Inc., 2000)
Ten-year-old India Opal Buloni describes her first summer in the town of Naomi, Florida, and all the good things that happen to her because of her big ugly dog Winn-Dixie.